What Are the Channels Through Which External Debt Affects Growth? - Poirson, Helene; Pattillo, Catherine; Ricci, Luca. (Washington, D.C. : International Monetary Fund, 2004)
This paper investigates the channels through which debt affects growth, specifically whether debt affects growth through factor accumulation or total factor productivity growth. It also tests for the presence of nonlinearities in the effects of debt on the different sources of growth. We use a large panel dataset of 61 developing countries over the period 1969-98. Results indicate that the negative impact of high debt on growth operates both through a strong negative effect on physical capital accumulation and on total factor productivity growth. On average, for high-debt countries, doubling debt will reduce output growth by about 1 percentage point and reduce both per capita physical capital and total factor productivity growth by somewhat less than that. In terms of the contributions to growth, approximately one-third of the effect of debt on growth occurs via physical capital accumulation and two-thirds via total factor productivity growth. The results are generally robust to the use of alternative estimators to control (to different extents) for biases associated with unobserved country-specific effects and the endogeneity of several regressors, particularly the debt variables. In particular, the results are shown to be compatible with a simultaneous significant effect of growth on debt ratios, as suggested by Easterly (2001).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet